Механізми підвищення ефективності участі України у міжнародних економічних інституціях - Перельотіна, Лілія Олександрівна; Perelotina, Liliia (ЦНТУ, 2021)
Кваліфікаційна робота присвячена дослідженню ефективності участі України у міжнародних економічних інституціях. Визначено базові принципи співпраці України з міжнародними організаціями. З’ясовано пріоритети, етапність та програми кредитування України Міжнародним валютним фондом. Оцінено результативність зовнішньої торгівлі України в умовах співпраці в межах СОТ. Обґрунтовано пропозиції щодо підвищення ефективності участі України у міжнародних економічних інституціях. Qualifying work to the research of Ukraine’s participation efficiency in international economic institutions. The basic principles of cooperation of Ukraine with international organizations are determined. The priorities, stage and programs of Ukraine’s lending by the International Monetary Fund are outlined. The effectiveness of Ukraine’s foreign trade in terms of cooperation within the WTO is evaluated. The proposals concerning increasing the effectiveness of Ukraine's participation in international economic institutions are substantiated.
Mechanisms for Improving the Effectiveness of Ukraine's Participation in the International Economic Institutions
Keywords: міжнародна економічна інтеграція; інституції; international economic integration; institutions